2012
DOI: 10.1016/j.ijmyco.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for multidrug-resistant tuberculosis in urban Pakistan: A multicenter case–control study

Abstract: A TB patient in the house or a history of prior TB treatment was strongly associated with MDR-TB in this study. Furthermore, younger age, male gender, Sindhi ethnicity and poor educational attainment entailed a high risk for MDR-TB. Targeted educational intervention for patients and their contacts may minimize the noncompliance with prescribed TB treatment and lessen MDR-TB magnitude in settings like Karachi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
30
3
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 15 publications
8
30
3
6
Order By: Relevance
“…The irregular medication caused disease relapse and drug-resistant Mtb became the dominant bacteria. The cavity was also another risk factor in our report, which In accordance with the study of Ahmad AM et al [16]. There were lots of drug-resistant Mtb in the cavity, so the Mtb might spread easily.…”
Section: Discussionsupporting
confidence: 91%
“…The irregular medication caused disease relapse and drug-resistant Mtb became the dominant bacteria. The cavity was also another risk factor in our report, which In accordance with the study of Ahmad AM et al [16]. There were lots of drug-resistant Mtb in the cavity, so the Mtb might spread easily.…”
Section: Discussionsupporting
confidence: 91%
“…This study conducted an analysis of sputum samples from patients with presumed MDR-TB and identified a high percentage of MDR-TB strains. One explanation may be close contact with known TB and MDR-TB patients, an association that was reported in several studies [9][10][11][12]. However, other risk factors associated with MDR-TB may be age, previous history of TB, HIV coinfection and alcohol consumption but not TB contact as reported elsewhere [13].…”
Section: Discussionmentioning
confidence: 87%
“…Penelitian Ahmad (2012), menyebutkan bahwa laki-laki dianggap relatif tidak peduli daripada wanita terkait asupan OAT secara teratur, dan fakta ini mungkin menyebabkan lebih banyak laki-laki yang menderita TB MDR. Hal ini sejalan dengan penelitian Maharatta (2010) yang menyatakan bahwa TB MDR terbanyak ditemukan pada jenis kelamin lakilaki dibandingkan perempuan, baik pada kelompok kasus maupun kontrol di dalam penelitian tersebut.…”
Section: Dataunclassified
“…Keluarga yang mempunyai pendapatan di bawah Upah Minimum Regional (UMR) akan mengkonsumsi makanan dengan kadar gizi yang tidak mencukupi kebutuhan bagi setiap anggota keluarga sehingga mempunyai status gizi yang kurang dan akan menjadikan risiko terkena penyakit infeksi TB MDR (Aderita, 2016). Pada penelitian Ahmad (2012) menyebutkan bahwa pendapatan rendah berisiko 3 kali untuk kejadian TB MDR (OR= 3,95%CI= 1,3-7,1). Berdasarkan hasil penelitian menunjukkan bahwa variabel pendapatan memiliki interval kepercayaan 1,133-4.317 (tidak mencakup angka 1) dan p value sebesar 0,030 < α (0,05), yang artinya ada hubungan antara pendapatan dengan kejadian TB MDR.…”
Section: Dataunclassified